Towards a sustainable economic governance in the East Sea - An, Nguyen Tac; Ittekkot, Venugopalan (Vietnam Journal of Marine Science and Technology, 2020)
The East Sea and its resources play a crucial role in Vietnam’s 2030 and vision to 2045 development agenda. This new “marine economy” model brings with its enormous opportunities, but also challenges that need to be address for its effective implementation especially under the complex geopolitical situation in the East Sea. Based on information from the last three decades, this paper describes the status and potential of marine economic sectors in Vietnam and suggests steps to maximize benefits and towards a sustainable development. It outlines options for responding to the challenges at national, regional and international levels. They include: (i) Coordination of coastal and marine economic sectors, integrated ecosystem - based management practices, and a broad consensus among Vietnamese public, (ii) Mutually beneficial cooperation for the development of marine economic sectors and programs among ASEAN countries, and finally, (iii) Compliance with international law and conventions. Such an approach will contribute to a harmonious and sustainable use of the East Sea for the benefit of the people in ASEAN nations, and of the world at large.